Kontribusi Pembelajaran Pendidikan Agama Islam Terhadap Peningkatan Pemahaman Konsep-Konsep Kewarganegaraan Pada Mahasiswa Program Studi Pendidikan Agama Islam STAI Al-Amin Dompu - Fitriani (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
This study aims to examine the contribution of Islamic religious education learning to increasing understanding of citizenship concepts in students of the Islamic religious education study program STAI Al-Amin Dompu. The research method used is quantitative with regression analysis techniques. The research sample was students of the Islamic religious education study program at one of the state universities in Indonesia. The results showed that learning Islamic religious education contributed positively and significantly to the students understanding of civic concepts. This is shown by the positive and significant value of the regression coefficient, as well as the value of the coefficient of determination, which shows that about 60% of the variation in the understanding of civic concepts can be explained by the learning of Islamic religious education. Therefore, the results of this study can provide recommendations for educational institutions to strengthen and improve Islamic religious education learning to increase understanding of citizenship concepts in students of Islamic religious education study programs